Students behavioural intention to use online consultation system the case of studlec meet system / Mohamad Rahimi Mohamad Rosman ...[et al.]. - Mohamad Rosman, Mohamad Rahimi; S Baharuddin, Nurfatihah; Razlan, Noor Masliana; Ismail, Nurul Najwa; Kamarudin, Nur Syahdah; Zawani, Zaitil Aqilah (2021)
The effect of COVID-19 causes a lot of stress to the communities, especially to the education industry. Educators and students were forced to embark into the unknown territory through open distance learning (ODL) initiative. Lack of Internet facilities, poor infrastructure, slow devices, and abundance of works cause a lot of stress to the students, especially to those that reside in the rural area. Therefore, StudLec Management System was developed based on rapid application of development methodology. However, there is no subsequent research being conducted to investigate user behavioural intention to use the online consultation management system. Therefore, a quantitative research methodology was adopted to identify the level of user behavioural intention in using online consultation management system. Data were analysed based on descriptive statistics. Findings show that the development of StudLec can help students to manage their time, have proper consultation with their lecturers, as well as reduce stressful conditions resulting from the pandemic